2019
DOI: 10.1111/nph.15813
|View full text |Cite|
|
Sign up to set email alerts
|

Tetranins: new putative spider mite elicitors of host plant defense

Abstract: Summary The two‐spotted spider mite (Tetranychus urticae) is a plant‐sucking arthropod herbivore that feeds on a wide array of cultivated plants. In contrast to the well‐characterized classical chewing herbivore salivary elicitors that promote plant defense responses, little is known about sucking herbivores’ elicitors. To characterize the sucking herbivore elicitors, we explored putative salivary gland proteins of spider mites by using an Agrobacterium‐mediated transient expression system or protein infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 44 publications
(62 reference statements)
0
25
0
Order By: Relevance
“…However, the molecular role of these effector molecules is yet to be determined. Recently, two novel proteins termed tetranin 1 and 2 (Tet1 and Tet2), which are located in the salivary glands of spider mites and have been shown to induce defenses in the host plants, have been characterized [58]. The infiltration of recombinant Tet1 and Tet2 proteins in bean leaves elicited early cellular responses such as cytosolic Ca 2+ influx, membrane depolarization and reactive oxygen species (ROS) production.…”
Section: Inducible Defenses: Plant Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the molecular role of these effector molecules is yet to be determined. Recently, two novel proteins termed tetranin 1 and 2 (Tet1 and Tet2), which are located in the salivary glands of spider mites and have been shown to induce defenses in the host plants, have been characterized [58]. The infiltration of recombinant Tet1 and Tet2 proteins in bean leaves elicited early cellular responses such as cytosolic Ca 2+ influx, membrane depolarization and reactive oxygen species (ROS) production.…”
Section: Inducible Defenses: Plant Perceptionmentioning
confidence: 99%
“…So far, most of the information on the early defense events comes from studies on plant-insect interaction. Also, some reports have demonstrated that T. urticae infestation produces cell damage that leads to alterations in cytosolic Ca 2+ levels and Vm variations accompanied by ROS production [58]. Accumulation of ROS and phenolic compounds at the wounding sites caused by T. urticae in barrelclover (Medicago truncatula) and thale cress plants have been reported [2,[68][69][70] and ascorbate, in response to T. urticae infestation.…”
Section: Inducible Defenses: Early Signalling Eventsmentioning
confidence: 99%
“…A family of 13 secreted salivary T. urticae proteins, referred to as SHOT, was shown to be exhibit strong host-dependent transcriptional plasticity ( Jonckheere et al., 2018 ). Moreover, two additional secreted spider mite proteins, referred to as tetranins, were shown to upregulate plant defenses ( Iida et al., 2019 ). In contrast, two salivary proteins, referred to as effector 28 and 84, were shown to suppress plant SA ( Villarroel et al., 2016 ) and JA defenses ( Schimmel et al., 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics and metabolomics studies have identified putative protein effectors coming from mite feeding that may be recognized by the plant defence system to initiate a successful plant defence response or in other cases, used by the spider mite to interfere and supress the plant defence system. Several pioneering works identified (i) two salivary proteins named as effectors 28 and 84, which are present in T. urticae and T. evansi , have been involved in suppression of JA and SA-dependent responses, (ii) a family of mite secreted salivary proteins referred as SHOT, which are produced depending of the host identity, and (iii) two secreted proteins named tetranins which could upregulated plant defences [ 14 , 18 , 19 , 20 , 21 ]. Moreover, spider mites may induce defence responses in systemic leaves and some strains and species of mites as T. evansi are able to suppress or reduce tomato defence responses [ 17 , 22 , 23 ], uncovering the complexity of the plant–spider mite interaction.…”
Section: Introductionmentioning
confidence: 99%